2014
DOI: 10.1371/journal.pone.0085424
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii Seroprevalence in Small Ruminants in The Gambia

Abstract: BackgroundQ fever is a zoonosis caused by Coxiella burnetii, a Gram negative bacterium present worldwide. Small ruminants are considered the main reservoirs for infection of humans. This study aimed to estimate the extent of C. burnetii infection among sheep and goats in part of The Gambia.Methodology/Principal FindingsThis survey was carried out from March to May 2012 at two areas in The Gambia. The first area comprised a cluster of seven rural villages situated 5–15 km west of Farafenni as well as the local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
24
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 30 publications
7
24
2
Order By: Relevance
“…16 Included in the few studies from African countries are reports of antibodies against C. burnetii in the sera of 1-24% of humans in 7 west African countries: 17 30.9% of humans, 28.3% of cattle, 18.2% of sheep and 32% of goats in Kenya, 18 24.2% of goats and 18.5% of sheep in Gambia, 19 C. burnetii DNA in the blood of 7.8% of cattle and 7.5% of goats in Tanzania, 20 and 0.3% of febrile patients in Algeria and 0.4% in Senegal 21 . A previous study performed nearly half a century ago in Ethiopia reported the detection of C. burnetii in 5.3% of Amblyomma variegatum and 10.8% of Hyalomma truncatum ticks.…”
mentioning
confidence: 99%
“…16 Included in the few studies from African countries are reports of antibodies against C. burnetii in the sera of 1-24% of humans in 7 west African countries: 17 30.9% of humans, 28.3% of cattle, 18.2% of sheep and 32% of goats in Kenya, 18 24.2% of goats and 18.5% of sheep in Gambia, 19 C. burnetii DNA in the blood of 7.8% of cattle and 7.5% of goats in Tanzania, 20 and 0.3% of febrile patients in Algeria and 0.4% in Senegal 21 . A previous study performed nearly half a century ago in Ethiopia reported the detection of C. burnetii in 5.3% of Amblyomma variegatum and 10.8% of Hyalomma truncatum ticks.…”
mentioning
confidence: 99%
“…Moreover, subclinical infection in carrier animals is typical (Saegerman et al 2015). Serological methods, such as immunofluorescence assay (IFA) and ELISA, have been widely used for Q fever diagnosis (Ni et al 2011, González-Barrio et al 2013, Klaasen et al 2014, Shin et al 2014. We used the ELISA method because of its convenience and high sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Humans are infected primarily by inhaling an aerosol contaminated with material from the urine or feces of infected animals (Esmaeili et al 2014, Schimmer et al 2014. People engaged in livestock breeding have a particularly high seroprevalence (Guatteo et al 2011, Klaasen et al 2014. Ticks are the main reservoir hosts, but mammals, birds, and other arthropods also play an important role in transmission (Ioannou et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations